Impact of Green Practices on the Financial Performance: A Study of Indian Automobile Companies - Kour, Manjit; Kaur, Rajinder; Bhullar, Arshan; Chaudhary, Ritika (International Journal of Economics and Financial Issues, 2020)
The green Practices have established a lot of implications in modern business. Green specifies purity through fairness in price, quality and worth in dealings. Green practices focus on producing and promoting products to satisfy the wants and needs of the consumers. Automobile industry is beginning to adopt green practices to get maximum benefit by brand enhancement, long-term cost savings, improved compliance with regulations and to appeal to higher investor interest and talent. But there is still scope and need to participate more in green technologies. In such a situation, the automobile industry is facing dual pressure i.e., to maintain the financial performance of the firm in the long run and to save the environment at the same time. This paper is an effort to analyze the impact of green practices adopted on the financial performance of the automobile companies in India. For this study a structured questionnaire is administered to a sample of 285 supply managers of the automobile industry in India. SEM (Structural Equation Modelling) method is used to analyze the data. In the results, it was found that four factors i.e., Integrated Environmental Management, Eco design, Technology Integration and Green Marketing had positive and significant influence on financial performance of the automobile companies. However, Pollution Prevention and Customer Oriented were found to have no significant influence on automobile companies’ financial performance. Keywords: Green Practices, Financial Performance, Automobile Companies, Eco Design, Integrated Environmental Management, Technology Integration. JEL Classifications: C83, L11, G40, L62 DOI: https://doi.org/10.32479/ijefi.10462